(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Economic theory indicates that the inequality in income distribution has negative impact upon poverty level, Yet, however, there are no studies show the relationship in an econometric model enables the decision maker to know the impact of inequality in income distribution in poverty levels, on the other hand, the time series data isn’t available about poverty line and on the rate of inequality in income distribution. This study tries to measure such relationship between poverty and inequality distribution through estimates time series of poverty line and Gini coefficient. In addition, the study attempts to evaluate the anti policies adopted by Iraqi government to eliminate poverty and inequality.